PENGUKURAN TINGKAT PRODUKTIVITAS PADA BAGIAN PRODUKSI DI INDUSTRI MIE âSAMI RASAâ DENGAN MENGGUNAKAN METODE OBJECTIVE MATRIX (OMAX) (Studi Kasus di Industri Mie âSami Rasaâ, Solo) - , OKFRIYANTO ISFATTHONI A.; Ir. Pujo Saroyo, M. Eng. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Industry noodles \"Sami Rasa\" is a company which produces the region's oldest dry noodles Jebres, Surakarta. The company is still a small to medium sized businesses with 16 workers rely. Tool or machine used is still modest. Even the steaming noodle factory designed by the owner himself. With the simplicity of a tool or machine used the very important role of productivity measurement is applied. This is done so that the company is still able to monitor the level of productivity is constant even though the company is still using simple tools or machines. So the company is able to compete with other companies. This productivity measurement method Objective Matrix (OMAX) is a system of partial productivity measures are being developed to monitor the productivity of each part of the company's productivity criteria in accordance with the existence of such parts. OMAX expected activity in all company personnel to assess, improve and maintain because this system is a measurement system that delivered directly to the parts of the industrial process unit. The final results of the measurements with OMAX method is a single value that states the achievement indicators of productivity in each period of productivity. In Mie Industry \"Sami Rasa\" criteria that affect the productivity is the amount of raw materials used, the amount of good product produced, the number of products produced, the number of total hours worked, the number of labor absenteeism, and total number of workers. Productivity level measurement results obtained highest achievement indicator value in July 2012 was 504.72 with an increase of the productivity level of the early indicators of achievement 341.65%. As for the lowest achievement indicators occurred in March 2012 was 109.51 with a decrease in the level of productivity of 4.17% of the initial indicators of achievement.